Rancang Bangun Sistem Informasi Pemesanan Kue Kota Pontianak Menggunakan Metode Waterfall - Purwaningtias, Deasy; Risdiansyah, Deni; Maulana, Muhammad Sony; Sasongko, Agung (Building of Informatics, Technology and Science (BITS), 2021)
Business growth in Indonesia continues to increase, as evidenced by the many new business fields that continue to emerge. One of these business fields is the bakery business. These business actors are only carried out by large producers, traditional micro small and medium enterprises have turned out to be the biggest contributors to this type of business. It is evident from 100% of these business activists that around 60% of their businesses are carried out by traditional micro small and medium enterprises. Not a few business actors in the bakery sector run their business conventionally which has an impact on their income. Whereas the existence of information systems in the world of business and management is to serve various needs and can be the key to better management and can be a success in running the business itself. For this reason, this study aims to create a website-based cake ordering information system. The software development method used in this research is the waterfall method. This information system is built using the CodeIgniter Framework. With this system, it is hoped that it can help customers in finding information on ordering cakes easily in Pontianak City quickly and accurately